PENGARUH IMPLEMENTASI GREEN ACCOUNTING DAN ENVIRONMENTAL PERFORMANCE TERHADAP SUSTAINABLE DEVELOPMENT DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERATING - , Meilda Wiguna, Zhahirah Noni Alfianisah , Hardi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to examine the effect of implementing green accounting and environmental performance on sustainable development with corporate social responsibility as a moderating variable. The population of this study were manufacturing companies that went public which were listed on the Indonesia Stock Exchange (IDX) in the basic industry and chemical sub-sectors in the 2016-2020 period. The research sample was selected using purposive sampling method. Data were obtained through data from the official website of the Indonesia Stock Exchange and other related websites and by studying literature related to research issues, both print and electronic media. The data analysis technique used in this study is descriptive statistics and Partial Least Square (PLS). PLS is a variance-based SEM statistical method designed to solve multiple regression when data problems occur, such as small study sample sizes, missing data and multicollinearity. PLS is an alternative approach that switches from a covariance-based SEM approach to variance (Ghozali and Latan, 2015: 5). Data processing uses Microsoft Excel 2013 and SmartPLS 3.0 software. The results of the research show that the implementation of green accounting and environmental performance influences sustainable development. Likewise, corporate social responsibility can moderate the influence between the implementation of green accounting and environmental performance on sustainable development. Keywords: Implementation Green Accounting, Environmental Performance, Sustainable Development And Corporate Social Responsibility.